[2+2] Photo-cycloadditions for polymer modification and surface decoration - Junkers, Tanja (European polymer journal, 2015)
[Display omitted] •[2+2] Cycloaddition reactions are efficient conjugation tools for precision polymer design.•By using flow chemistry, reaction rates can be significantly accelerated.•Polymer modification as well as surface ligation is accessible via [2+2]. Photo-induced reactions play an important role in precision polymer design. Photoreactions are often cost-effective reactions that proceed under relatively mild reaction conditions. Additionally, photo reactions add spatial and temporal control over reactions, which gives rise to a large number of applications that would otherwise be inaccessible. Among the various photochemistries available, [2+2] cycloadditions are a prominent example for effective conversions. In the field of polymer chemistry, such reactions are often used for crosslinking. If reaction conditions are chosen carefully, they can, however, also be employed for advanced polymer transformations, such as polymer endgroup modification or specific ligation to substrates. Especially when applying flow chemistry approaches, very high reaction efficiencies are gained, bringing [2+2] cycloadditions close in use to other well known click-like techniques such as thiol–ene chemistry.